Habilidades Sociales en los Estudiantes de la Unidad Educativa “José María Román”. Riobamba. Octubre 2017-Marzo 2018. - Angulo Bautista, Yuri Edith (2018)
The objective of the research project was to determine the social skills of the 10th EGB students of the "José María Román" Educational Unit through the application of the Goldstein social skills checklist. Theoretically, it was studied that social skills are a set of behavioral competencies that enable the human being to have positive social relationships with others and face them in an effective and adaptive way, which requires their social context, these aspects contribute significantly, for a part to the understanding of a behavior on the part of the people who are in the environments where the individual develops and on the other hand to the effective social development in different areas. Methodologically it had a non-experimental design, by the descriptive level, by the type of cross-sectional study, the population were students of the Educational Unit "José María Román", the sample was non-probabilistic and intentional that corresponded 30 men and 25 women, the technique used was a psychometric test. The instrument used was Goldstein's social skills checklist, which were very helpful in obtaining and collecting data. It is concluded that the students have deficiencies and competences of social skills and when making the comparison it was possible to identify that the parallel A has a higher level of social skills development.